Origenes’ Welten Frühchristliche Kosmologie im Spannungsfeld zwischen Platonismus und Heilsgeschichte - Habermehl, Peter (Hyperboreus, 2015)
In nuce the idea of a perpetual cosmic circle and the eternal return of our world was present in several ancient religions and philosophical schools – namely Plato, Pythagoreans and Stoa. But surprisingly enough it appears as well in a seminal Greek theologian of the early church: Origen. He assumed a transcendent creation of eternal spiritual beings close to God, but with a free will and an inner nature prone to change. ‘With time’ these beings became alienated from God, deteriorated into souls and ‘fell’ into our ﬁnite physical world, which God’s Son created for them as a place of education. A long journey through different bodily existences is their chance to return into God’s spiritual realm. But one material cosmos does not sufﬁce to complete this process of amelioration. To continue the puriﬁcation, God calls into existence another physical world, and still another, and so on for almost endless times, until ﬁnally, after uncountable cosmic cycles, the entire spiritual creation is puriﬁed and reunited with the creator (including Satan) – and with the unsettling prospect that this whole process might start all over again. These unheard-of cosmological speculations brought the synthesis of Platonism and Christianity to its ancient acme.